Atividades biológicas e composição química dos óleos essenciais de Achyrocline satureoides (Lam) DC. e Ageratum conyzoides L. encontradas no semiárido baiano - Gonçalves, Jacqueline Miranda (2015)
Essential oils are complex mixtures of various isolates of plant secondary metabolites. Due to the increased use of these aromatic compounds, research has been developed, and the development of new products. This study analyzed the antimicrobial, cytotoxic and immunomodulatory activities in addition to the phytochemical profile of essential oils Achyrocline satureoides and Ageratum conyzoides. The micro-organisms most sensitive to oils were Staphylococcus aureus CCMB 262 and Candida kruzei CCMB 287. The essential oil of A. conyzoides was considered non-toxic in the tested conditions. In the assessment of the immune response induced by oils, although they were not statistically significant differences between the concentrations tested and control, it was observed that the essential oils inhibited the production of IL-8 and IL-12 cytokines with exception of the species A. satureoides at a concentration of 100 mg / mL. This behavior may suggest the capacity reduction of the inflammatory response. The chromatographic analysis of essential oils of A. satureoides demonstrated a chemical profile consistent with the literature where the major components were α-Pinene, E-caryophyllene, α-copaene, α-humulene, d-cadinene. Since the analysis of oils A. conyzoides showed conflicting results in the literature which suggests a new chemotype, since the presence of precocenos the chemical analysis was not observed.